Focusing on Actors, Scaling‐Up, and Networks to Understand Co‐Production Practices: Reporting from Berlin and Santiago - Moya-Ortiz, D (Cogitatio Press, 2024)
In different policy agendas, such as the New Urban Agenda and the Sustainable Development Goals, co‐production is introduced as a desirable urban planning practice to validate the engagement and inclusion of diverse actors/networks. Nevertheless, some scholars argue (e.g., Watson, Robinson) that the Western planning approach faces difficulties incorporating rationalities beyond the Global North–South division. In this context based on the research project DFG‐KOPRO Int for the German Research Foundation on Chilean and German cases and the local context, this article seeks to explore how local groups are undertaking co‐production, which means of legitimacy are used, and which socio‐spatial results develop. In doing so, the research focuses firstly on the negotiation processes (governance) between stakeholders by undertaking network analysis and, secondly, on understanding the impulse for urban development by analysing the project’s socio‐spatial material patterns. Chile’s neoliberal context and the case studies showcase diverse cooperative forms that try to close governance gaps within strong political struggles. In the German context, actors from different areas, such as cultural institutions, universities, and private actors undertake diverse mandates for testing regulatory, persuasive, or financial instruments. As different as local realities are, the overall results show that co‐production occurs mostly in highly contested fields such as housing projects and highlights a three‐part constellation of actors—state, private, and civil society—in urban development. However, negotiation processes take place, ranging from conflictive to cooperative. Hence, co‐production challenges prevailing social and political structures by providing an arena for new forms of collective and pluralistic governance. © 2024 by the author(s), licensed under a Creative Commons Attribution 4.0 International License (CC BY).